Исследование условий самовращение резца на основе компьютерного моделирования его контактного взаимодействия с горной породой - Майстренко, А.Л.; Кущ, В.И.; Шестаков, С.И.; Свешников, И.А.; Заболотный, С.Д.; Беспалов, С.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
A theoretical model has been developed that describes the behavior of self-rotating cutters during their contact interaction with a rock. For self-rotating cutters of the «CHAMPION Equipment Co. (CEC)», USA, with cylinder-conic carbide rock destruction elements, the values of the normal Py and tangential Pz components of the cutting force have been defined. The values are in good agreement with the experimental data. The effect of the tool cutting edge blunting on the cutting force components has been studied. In the mode of a computerized experiment, the range of the cutting parameters variation has been assessed, at which the conditions of the cutter self-rotation are met.